RE4CH: Engenharia de requisitos para saúde conectada: Lidando com práticas ágeis e rastreabilidade - Arnaud, Júlia Cibelle Freire de Queiroz (2017)
The number of health information systems is increasing in quantity and complexity, and their quality is essential to improve the quality of the services delivered to the population. Normally, the development of medical device software presents requirements that normally are not addressed by the traditional software development of non-safety critical industry. In this sense, projects of health information systems start to face new challenges imposed by regulators, society and suppliers since they start to interact with medical devices, personal health devices and diagnostic solutions. Requirements engineering processes are very important for the reduction of the involved risks in the development of these systems. Most agile processes used by several companies, although following well established activities for software development, have some gaps in the requirements engineering activities, turning the way in which requirements are developed in the context for health often incomplete. Health system development should be supported by an appropriate requirements engineering process, which in addition to guiding the development process, also fits in the treatment of specific requirements that these software products need. This work proposes the definition of a requirements engineering process that enables the development and management of requirements in a traceable way, while at the same time aligning with the agile development process. The process defines activities, inputs, outputs and guidelines that, in an integrated way and guides the requirements engineering in an effective way. Finally, an experimental study is presented in the context of health information systems to evaluate the viability of the proposed process.